Sosialisasi Mitigasi Bencana Geologi SMAN 23 Jakarta - Yusraida Khairani Dalimunthe; Afiat Anugrahadi; Agus Guntoro (Jurnal Migasian, 2022)
The purpose of this Community Service is to provide knowledge about disaster mitigation, especially the earthquake and tsunami disaster at SMAN 23 Jakarta. This activity was carried out on January 21, 2022 through a zoom meeting which was attended by students of SMAN 23 Jakarta from the MIPA and IPS majors. This activity was initiated by providing a pre-socialization questionnaire through google form which aims to determine the knowledge of SMAN 23 Jakarta students related to disaster mitigation, especially the earthquake and tsunami disaster before socialization, then carried out socialization in the form of exposure to disaster mitigation through presentations and videos, then ended by giving back the socialization evaluation questionnaire which aims to see how far the benefits felt by students and students of SMAN 23 Jakarta from the socialization that has been delivered. Through an evaluation questionnaire given to 11 students after socialization, it appears that there is an increase in the knowledge of students at SMAN 23 Jakarta, where there is an increase of 18.2% in knowledge of students and students related to the mechanism of destruction caused by earthquakes, then there is an increase of 9, 1% knowledge of students related to tips for handling in the event of an earthquake, followed by an increase of 18.2% related to symptoms and early warning of a Tsunami and an increase of 9.6% in knowledge of students and students regarding tips for handling in the event of a Tsunami. From the questionnaire, it can be concluded that this socialization activity is useful and increases the knowledge of SMAN 23 Jakarta students regarding disaster mitigation, especially the earthquake and tsunami disaster, which is then expected to be able to fortify themselves if at any time an earthquake and tsunami disaster occurs in their neighborhood.